Decolonial Reflections in Latin American Metal Music: Religion, Politics and Resistance - Varas-Díaz, Nelson; Morales, Eric (Théologiques, 2018)
Latin America’s history is deeply embedded in the experience of coloniality. Still, its history cannot be told without stories of resistance to its colonial experience. This resistance takes many shapes, from armed conflict to the use of the arts, and addresses many consequences of coloniality. We aim to explore how metal music in Latin America has been used to challenge the colonial legacy of the region. Although coloniality has had many implications (e.g., political, economical, environmental), we focus on the specific challenge towards religion (Christianity in particular) as a strategy to critically assess this colonial legacy. We present three thematic examples that highlight this critical approach in Latin American metal towards coloniality in general, and Christian religion in particular. These include : 1) highlighting the presence of indigenous populations in the region, 2) reframing of religious culture as an act of resistance, and 3) linking religion to current colonial politics.